Adaptation and Validation of the We-ness Questionnaire in a Turkish Sample - Üçok, S. Burcu Özgülük; Aydoğan, Didem; Topcu, Çiğdem; Randall, Ashley K. (Bartın Üniversitesi, 2024)
We-ness refers to a feeling of unity between partners, and a mental representation of the relationship as a shared identity. Despite its relevance, research on understanding partners' sense of we-ness is limited in collectivist cultures such as Turkey. A psychometrically sound measure of we-ness is needed to increase research on we-ness. Hence, this study aimed to examine the basic psychometrics of the We-ness Questionnaire. Two hundred and nineteen married individuals participated in this study and completed the Turkish version of the We-ness Questionnaire along with the Turkish version of the Couple Satisfaction Index, Self-developmental Orientation Subscale, and Inter-relational Orientation Subscale of the Balanced Integration and Differentiation Scale. The one-factor structure of the We-ness Questionnaire was confirmed via confirmatory factor analysis. Adequate convergent and discriminant validity besides satisfactory internal consistency results were achieved as a result of these analyses. Based on the preliminary investigation, the Turkish We-ness Questionnaire proved to be a promising measure of we-ness in Turkish married individuals. As such, the findings of this study were discussed regarding the previous literature, limitations were pointed out, and suggestions for future research were given.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar